Pengaruh Content Marketing, Influencer Marketing dan Electronic Word of Mouth (e-WOM) terhadap Minat Beli produk Skincare Bromen pada Aplikasi TikTok di Surabaya - Triana, Brahma Nanda Putra; Ida Ayu Sri Brahmayanti (Nirta Learning Centre, 2025)
Abstract. This study aims to examine the influence of Content Marketing, Influencer Marketing, and Electronic Word of Mouth (e-WOM) on Purchase Intention for Bromen skincare products on the TikTok application in Surabaya. The research employs a quantitative approach with purposive sampling, involving 100 consumers of Bromen skincare products who use TikTok. Data were collected through a Likert-scale questionnaire and analyzed using validity and reliability tests, classical assumption tests, multiple linear regression, t-tests (partial), F-tests (simultaneous), and determination coefficient analysis. The results indicate that Content Marketing (t-value = 6.145; p < 0.05) and Influencer Marketing (t-value = 3.682; p < 0.05) have a significant influence on Purchase Intention, whereas e-WOM does not show a significant effect (t-value = 1.720; p > 0.05). Simultaneously, the three variables have a significant influence on Purchase Intention (F = 125.042; p < 0.05), contributing 79% to the variance, while the remaining 21% is influenced by other factors outside the scope of this study. These findings imply the need to enhance Content Marketing strategies, expand collaborations with influencers, and optimize e-WOM to boost consumer Purchase Intention. Keywords: Content Marketing, Influencer Marketing, Electronic Word of Mouth, Purchase Intention.